Participatory Approaches to the Planning of Literacy Education in Botswana - Tonic Maruatona (Adult Education Research Conference, 2002)
This paper is a critique of planning in the Botswana National Literacy Program, it outlines activities of the program and demonstrates how it reproduces social inequality and suggests participatory strategies to strengthen literacy education in Botswana.